2018
DOI: 10.1002/pc.25073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hybridization of Carboxyl‐Terminated Acrylonitrile Butadiene Liquid Rubber and Alumina Nanoparticles on the Fracture Toughness of Epoxy Nanocomposites

Abstract: The aim of this work was to study the effect of carboxyl‐terminated acrylonitrile butadiene (CTBN) liquid rubber and alumina nanoparticles (Al2O3) on the fracture toughness of an epoxy resin. Hybrid nanocomposite samples were prepared by the inclusion of the optimum concentration of CTBN (15 phr) and 0–10 phr Al2O3 into the epoxy matrix. Samples were examined using Fourier transform infrared spectroscopy, scanning electron microscopy, and fracture toughness test. Fractal dimension values were also estimated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…[42] Based on the isothermal surface potential decay theory, the distribution of trap energy levels is shown in Figure 16. The trap energy level and trap density in Figure 16 are calculated by Formulas (6) and (7). [43] It can be found that the trap center energy level of the sample decreases with the time of zirconia deposition increasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] Based on the isothermal surface potential decay theory, the distribution of trap energy levels is shown in Figure 16. The trap energy level and trap density in Figure 16 are calculated by Formulas (6) and (7). [43] It can be found that the trap center energy level of the sample decreases with the time of zirconia deposition increasing.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, under the DC electric field, charges are easily accumulated in epoxy-based insulation materials, which directly affect the insulation properties and easily induce flashover phenomena. [5][6][7][8][9] Preceding theoretical researches showed that surface morphology and chemical element of insulating materials can affect the motion characteristics of surface charges, and then influence the flashover. [10][11][12][13] At present, methods for surface modification of polymers including surface group modification, surface fluorination, oxide film surface deposition, changing the surface morphology of materials, and organic coating synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all EPs are brittle [12][13][14]. Many tougheners such as carboxyl-terminated butadiene-acrylonitrile (CTBN) [15,16], core-shell rubber (CSR) particles [17,18], thermoplastic or thermoset polymers [19,20], and organicinorganic particles [21,22] have been incorporated to increase the toughness of EP resins. These tougheners decrease modulus, tensile strength, and glass transition temperature (T g ); so in order to enhance the mechanical and thermal properties, the toughened EPs are reinforced by nanosilica (NS) particles.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The GIL disk insulator is mainly made of epoxy resin composites doped with micro-Al 2 O 3 with a mass fraction of 60%, which has guaranteed the thermal, mechanical, and basic insulation requirements for the insulator. [5][6][7] However, the doping of Al 2 O 3 fillers has also reduced the surface insulation performance. Due to the obstruction of charge transport brought by filler Al 2 O 3 , the surface of the insulator would accumulate a large amount of net charge under longterm action of DC electric field, which would aggravate the distortion of surface electric field, thus to induce the accidents of flashover.…”
Section: Introductionmentioning
confidence: 99%
“…The flashover accident of the disk insulator can be the most severe one 1–4 . The GIL disk insulator is mainly made of epoxy resin composites doped with micro‐Al 2 O 3 with a mass fraction of 60%, which has guaranteed the thermal, mechanical, and basic insulation requirements for the insulator 5–7 . However, the doping of Al 2 O 3 fillers has also reduced the surface insulation performance.…”
Section: Introductionmentioning
confidence: 99%